Simultaneous Determination of Malachite Green, Chloramphenicols, Sulfonamides, and Fluoroquinolones Residues in Fish by Liquid Chromatography-Mass Spectrometry - Yongping Chen; Sudong Xia; Xianqin Han; Zhiru Fu (Journal of Analytical Methods in Chemistry)
A fast-analytical method using simplified extraction has been developed for the simultaneous determination of 42 compounds from 4 different classes of veterinary drugs (amphenicols, triphenylmethane, fluoroquinolones, and sulfonamides) in fish by reverse phase liquid chromatography-tandem mass spectrometry. The selection of extraction reagents was optimized using different types of microfiltration membrane, mobile phase, and LC column. Samples were extracted using 0.4% hydrochloric acid in acetonitrile and ethyl acetate and then were cleaned up using solid-phase extraction Cleanert Alumina N columns (500 mg) and Oasis hydrophilic-lipophilic balance (HLB) cartridges. The chromatographic separation was performed on a XR-ODS C8 column using a mobile phase of (A) 0.1% formic acid and 2 mM ammonium acetate and (B) 0.1% formic acid acetonitrile at a flow rate of 0.25 mL·min−1. The results indicated 67.7–112.8% recovery of 42 compounds with an intra- and interday relative standard deviations less than 10%. The limits of quantification for analytes were in the range of 0.3–1.0 μg kg−1 for samples which were satisfactory to support future surveillance monitoring. The method applicability was checked by analyzing 30 fish samples collected from local markets. Two fish samples surpassed the established MRL of 100 μg kg−1 with values of 104 μg kg−1 and 112 μg kg−1.